A Pragmatic Analysis Of English Advertisements A Case Study - Sri Haryani (Bangun Rekaprima, 2017)
A part of the study of language use is the study of language used in advertisement. It is of great interest since advertising language has a certain feature, which is persuasive in nature. The writer was interested in conducting a research concerning the language of advertising and analyzed it by using a pragmatic approach. The aim of the study is to find out how persuasive goals of the advertisements are expressed through the language. The analysis focuses on the illocutionary act and the application of cooperative principles in English advertisements. This paper consists of the theoretical background of pragmatics and the pragmatic analysis on English advertisements. The results of the research shows that: (1) the English advertisement persuades customers by providing information in the form of a report which implies an offer of products of goods or services; (2) the advertising texts studied in the discussion contains the kinds of illocutionary act and the cooperative principles; (3) the illocution power in the words of the English advertisement has the kinds of direct illocution and indirect illocution; and (4) the obedience and deviation of the cooperative principles occur in the advertising to propagate the products and services advertised.Kata Kunci: Pragmatic, Advertising, Illocutionary Act, Cooperative Principles, Utterance